Matrix-isolation and solid state low temperature FT-IR study of 2,3-butanedione (diacetyl) - Gómez-Zavaglia, Andrea (2003)
2,3-Butanedione (diacetyl) was studied by matrix-isolation and low temperature solid state FT-IR spectroscopy, supported by molecular orbital calculations undertaken at the DFT(B3LYP) and MP2 levels of theory with the 6-311++G(d,p) basis set. Both in the crystalline phase and in the matrices, the compound exists in the C2h symmetry trans conformation (O=C-C=O dihedral angle of 180°). This form corresponds to the single conformational state predicted by the theoretical calculations for the compound in vacuum. However, in the low temperature amorphous state, obtained by fast deposition of the vapour of the compound onto a suitable cold (9 K) substrate, as well as in the liquid and gaseous phases, spectroscopic features are observed that can only be explained by assuming that conformations without an inversion centre (C2 symmetry) do also contribute to the spectra. These results are in agreement with the experimental evidence that diacetyl has a permanent dipole moment (ca.1 Debye) in the vapour phase at room temperature and are here explained taking into consideration the influence of the low frequency large amplitude torsional vibration around the central C-C bond on the molecular properties.